Preparation method of anti-cracking and anti-corrosion concrete
By crushing, fermenting and heat treatment of kitchen residues with cement and fly ash, ultrafine fillers with porous structures are formed, and combined with pre-emulsion precursors and inorganic rust inhibitors to form a tough mesh structure, the problems of concrete cracking and corrosion are solved, and the effects of cracking and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202411444699.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-25
- Publication Date
- 2025-02-28
AI Technical Summary
Existing concrete is prone to cracking during the solidification and hardening process, and steel bar corrosion is prone to occur in salted environments in coastal areas.
By co-pulling, fermenting and granulating the kitchen residue with cement and fly ash, and being heat-treated and air-flowed, an ultrafine filler with a porous structure is formed, combining pre-emulsion precursors and inorganic rust inhibitors to form a tough mesh structure, improving the crack resistance and corrosion resistance of concrete.
The cracking and corrosion resistance of concrete is achieved. Through the formation of porous structures and tough mesh structures, the rust time of steel bars is delayed and the speed of steel bars is slowed down.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete, in particular to a method for preparing crack-resistant and corrosion-resistant concrete. Background Art
[0002] When concrete is used in coastal areas, coastal saline land, inland salt lake areas and other areas, the soil in these areas has high content of chloride ions and sulfate ions, which can penetrate or activate the oxide protective film on the surface of the steel bars, thereby creating conditions for electrochemical corrosion. The electrode potentials of various parts of the steel bars will be different, forming local batteries. Once the corrosion of the steel bars occurs, it will continue.
[0003] Existing concrete is prone to cracking during the preparation and use processes. When the concrete solidifies and hardens, the free water inside gradually evaporates from the surface to the inside, causing the concrete to gradually dry and shrink from the surface to the inside. When the tensile stress generated by the shrinkage is greater than the tensile strength limit of the concrete component, the concrete will crack. Summary of the invention
[0004] The purpose of the present invention is to provide a crack-resistant and corrosion-resistant concrete and a preparation method thereof, so as to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing anti-cracking and anti-corrosion concrete, comprising the following preparation steps: (1) Kitchen residues are sorted, bones are removed, and the residues are fed into a press to obtain wet materials. Cement 0.3-0.5 times the mass of the wet materials and fly ash 0.9-1.6 times the mass of the wet materials are added, and the residues are fed into a crusher to be crushed to a particle size of 1-3 mm. Intermediate material A with a diameter of 5-10 mm is obtained by granulation. The bacterial liquid and intermediate material A are mixed at a mass ratio of 1:1000, and fermented at 37-55°C, 80 rpm, and a ventilation volume of 4-8 L / min for 48-72 h. After drying at 100°C for 10 h, the mixture is heated to 200-250°C. , semi-carbonized for 4-8 hours, put into air flow mill, crushed for 20-30 minutes, taken out, activated at 400-500℃ for 20-30 minutes in a carbon dioxide-nitrogen atmosphere with a volume fraction of 15%, and obtained intermediate B; intermediate B and nitric acid solution were mixed at a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the grinding speed was 150-250rpm for 10-25 minutes, and then sodium nitrite aqueous solution 3-5 times the mass of intermediate B was added, and the grinding was continued for 10-25 minutes, filtered, and dried at 100℃ for 6 hours to obtain ultrafine filler; (2) Under stirring at 300 rpm, add the pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, and keep warm at 50-80°C for 1-2 h. During the insulation process, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate. Adjust the speed to 50-70 rpm and continue to keep warm for 2 h. During the insulation process, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 min, then add the remaining coarse aggregate and fine aggregate, and microsilica powder, and stir for 10 min to obtain crack-resistant and corrosion-resistant concrete.
[0006] Furthermore, in step (1), the press is used to press the product until the moisture content is between 20% and 30%.
[0007] Furthermore, the bacterial solution in step (1) is composed of Geotrichum candidum, lactic acid bacteria, white rot fungi, and Aspergillus niger in a volume ratio of 1:1:1:1, and the bacterial content is (1-9)×10 12 Pieces / mL.
[0008] Furthermore, in step (1), the powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.8-1.0 MPa.
[0009] Furthermore, the airflow of the airflow mill in step (1) is 15% carbon dioxide-nitrogen at 200°C.
[0010] Furthermore, the mass fraction of the nitric acid solution in step (1) is 15-35%.
[0011] Furthermore, the mass fraction of the sodium nitrite aqueous solution in step (1) is 4%.
[0012] Furthermore, the preparation method of the pre-emulsion precursor in step (2) is: hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water are mixed in a mass ratio of 50:20:0.5:80~50:30:0.5:95, stirred at 600 rpm for 15~30 min, and homogenized at a pressure of 30 MPa for 1 min.
[0013] Furthermore, in step (2), the mass ratio of the coarse aggregate, the pre-emulsion precursor, the cement, the fine aggregate, the ultrafine filler, the microsilica powder and the deionized water is 350-550:25-35:100-150:150-320:80-120:4-8:160-180.
[0014] Furthermore, the particle size of the microsilica powder in step (2) is 0.1-0.5 μm, and the silicon content of the microsilica powder is above 93%.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The present invention prepares concrete by mixing ultrafine filler, pre-emulsion precursor, cement, aggregate, microsilica powder and the like to achieve the effects of crack resistance and corrosion resistance.
[0016] Firstly, the present invention utilizes kitchen residues, cement and fly ash to be pulverized, fermented and granulated together, and after heat treatment, moisture and volatile substances are gasified, and part of the internal organic matter is decomposed to achieve semi-carbonization, a porous carbonized layer appears on the surface of the particles, while the toughness is retained inside, which can improve the anti-cracking effect of concrete; then the first grinding is carried out, and high-temperature CO2 airflow is used for pulverization, and the particle size is refined and initially activated at the same time, and then the CO2 temperature is further increased to enrich the number of micropores and form a porous structure, and then a secondary grinding is carried out, and dilute nitric acid and an inorganic rust inhibitor aqueous solution are used as grinding media in turn to increase the active groups such as hydroxyl and carboxyl on the surface of the ultrafine filler, and at the same time, through the capillary action of the surface pore size, the inorganic rust inhibitor is adsorbed in the pores of the ultrafine filler, effectively controlling the release of the inorganic rust inhibitor, which can delay the time when the steel bar starts to rust, slow down the speed of steel bar corrosion development, and achieve the anti-corrosion effect of concrete.
[0017] Secondly, the present invention utilizes hexaethylcyclotrisiloxane and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine to prepare a pre-emulsion precursor. After being mixed with cement and aggregate, part of the silicon-oxygen bonds are combined with the cement and aggregate surfaces, which is beneficial to enhancing the internal bonding force of the concrete and improving the crack resistance of the concrete. After heat treatment, the polymer forms a tough network structure. When the concrete is subjected to force and is about to crack, the cement separation is inhibited through the pulling effect of the network structure, and the anti-cracking performance of the concrete is improved. In addition, with the continuous addition of raw materials such as stirring and ultrafine fillers, the ultrafine fillers rely on surface active groups to generate hydrogen bonds with the organic silicon polymer, are adsorbed on the surface of the network structure, and are self-stacked, gradually expanding the network structure, prolonging the penetration time of the rust inhibitor, and further improving the anti-corrosion and anti-cracking performance of the concrete. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0019] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the anti-cracking and anti-corrosion concrete prepared in the following examples are as follows: Cracking resistance: The examples and comparative examples were made into standard test blocks according to GB / T50081. After 28 days of pouring, the total cracking area of the cracks on the standard test blocks was measured.
[0020] Anti-corrosion: Tested according to 7.1 fast chloride ion migration coefficient method in GB / T50082; tested against sulfate corrosion coefficient according to GB / T749.
[0021] Example 1 (1) Kitchen waste is sorted, bones are removed, and the waste is fed into a press, where it is pressed to a moisture content of 20 to obtain a wet material. Cement 0.3 times the mass of the wet material and fly ash 0.9 times the mass of the wet material are added, and the waste is fed into a crusher, where it is crushed to a particle size of 1 mm, and granulated to obtain an intermediate A with a diameter of 5 mm. The bacterial liquid and intermediate A are mixed at a mass ratio of 1:1000, fermented at 37°C, 80 rpm, and a ventilation volume of 4 L / min for 48 h, dried at 100°C for 10 h, heated to 200°C, semi-carbonized for 4 h, and fed into an air flow mill with an air flow of 200°C and a volume fraction of 15% carbon dioxide-nitrogen. , crushed for 20 minutes, taken out, activated at 400℃ for 20 minutes in a 15% volume fraction carbon dioxide-nitrogen atmosphere to obtain intermediate B; intermediate B and 15% mass fraction nitric acid solution were mixed in a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the grinding was carried out at 150rpm for 10 minutes, and then a 4% mass fraction sodium nitrite aqueous solution of 3 times the mass of intermediate B was added, and the grinding was continued for 10 minutes, filtered, and dried at 100℃ for 6 hours to obtain an ultrafine filler; the bacterial liquid was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 1×10 12 The powder feeding pressure of the air flow mill is 0.4MPa and the crushing pressure is 0.8MPa. (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water were mixed in a mass ratio of 50:20:0.5:80, stirred at 600 rpm for 15 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor; (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 50°C for 1 hour, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 50 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 350:25:100:150:80:4:160.
[0022] Example 2 (1) Kitchen residues were sorted, bones were removed, and the residues were fed into a press and pressed to a moisture content of 25% to obtain wet materials. Cement 0.4 times the mass of the wet materials and fly ash 1.2 times the mass of the wet materials were added, and the residues were fed into a crusher and crushed to a particle size of 2 mm. Intermediate material A with a diameter of 8 mm was obtained by granulation. The bacterial liquid and intermediate material A were mixed at a mass ratio of 1:1000, fermented at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dried at 100°C for 10 h, heated to 220°C, semi-carbonized for 6 h, and fed into an air flow mill with an air flow of 200°C and a volume fraction of 15% carbon dioxide-nitrogen. Gas, crush for 25 minutes, take out, activate at 450℃ for 25 minutes in a 15% volume fraction carbon dioxide-nitrogen atmosphere to obtain intermediate B; mix intermediate B and 20% mass fraction nitric acid solution in a mass ratio of 1:3, grind at 200rpm for 18 minutes with a ball-to-material ratio of 15:1, add 4% mass fraction sodium nitrite aqueous solution 4 times the mass of intermediate B, continue grinding for 18 minutes, filter, and dry at 100℃ for 6 hours to obtain ultrafine filler; the bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 / mL; the powder feeding pressure of the air flow mill is 0.4MPa, and the crushing pressure is 0.9MPa; (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water were mixed in a mass ratio of 50:25:0.5:89, stirred at 600 rpm for 22 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor; (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 68°C for 1.5 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 60 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 420:30:120:250:100:6:170.
[0023] Example 3 (1) Kitchen residues were sorted, bones were removed, and the residues were sent to a press to be pressed to a moisture content of 30% to obtain wet materials. Cement 0.5 times the mass of the wet materials and fly ash 1.6 times the mass of the wet materials were added, and the residues were sent to a crusher to be crushed to a particle size of 3 mm. The intermediate A with a diameter of 10 mm was obtained by granulation. The bacterial liquid and the intermediate A were mixed at a mass ratio of 1:1000, fermented at 55°C, 80 rpm, and a ventilation volume of 8 L / min for 72 h, dried at 100°C for 10 h, heated to 250°C, semi-carbonized for 8 h, and sent to an air flow mill with an air flow of 200°C and a volume fraction of 15% carbon dioxide- The mixture was crushed with nitrogen for 30 minutes, and then taken out and activated at 500°C for 30 minutes in an atmosphere of 15% carbon dioxide-nitrogen by volume to obtain intermediate B; intermediate B and 35% nitric acid solution were mixed in a mass ratio of 1:3, and the ball-to-material ratio was 15:1. After grinding at 250rpm for 25 minutes, a 4% sodium nitrite aqueous solution with a mass fraction of 5 times that of intermediate B was added, and the grinding was continued for 25 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler; the bacterial solution was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 9×10 12 The powder feeding pressure of the air flow mill is 0.4MPa and the crushing pressure is 1.0MPa. (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water were mixed in a mass ratio of 50:30:0.5:95, stirred at 600 rpm for 30 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor; (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 80°C for 2 h, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 70 rpm, continue to keep warm for 2 h, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 min, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 min, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 550:35:150:320:120:8:180.
[0024] Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press to a moisture content of 25%, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80rpm, and a ventilation volume of 6L / min for 56h, dry at 100°C for 10h, heat to 220°C, semi-carbonize for 6h, enter the air flow mill, the air flow is 200°C and the volume fraction of 15% carbon dioxide-nitrogen, powder After crushing for 25 minutes, take it out and activate it at 450℃ for 25 minutes in an atmosphere of 15% carbon dioxide-nitrogen by volume to obtain intermediate B; mix intermediate B and 20% nitric acid solution by mass ratio of 1:3, grind at 200rpm for 18 minutes with a ball-to-material ratio of 15:1, add 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B, continue grinding for 18 minutes, filter, and dry at 100℃ for 6 hours to obtain ultrafine filler; the bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.
[0025] Comparative Example 2 The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press until the moisture content is 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry at 100°C for 10 h, heat to 800°C, carbonize for 3 h, enter the air flow mill, and air flow is 200°C. The invention relates to a method for preparing an ultrafine filler. The method comprises the following steps: mixing the intermediate B and a nitric acid solution with a mass fraction of 20% at a mass ratio of 1:3, grinding the mixture at a ball-to-material ratio of 15:1 and 200 rpm for 18 minutes, adding a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of the intermediate B, and continuing to grind for 18 minutes. The mixture is filtered and dried at 100°C for 6 hours to obtain an ultrafine filler. The bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.
[0026] Comparative Example 3 The difference between Comparative Example 3 and Example 2 is that step (1) is changed to: sort the kitchen residues, remove the bones, put them into a press, press them to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, put them into a crusher, crush them to a particle size of 2 mm, and granulate them to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment them at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry them at 100°C for 10 h, and then heat them to 220°C. The mixture was semi-carbonized for 6 hours, activated at 450°C for 25 minutes in a carbon dioxide-nitrogen atmosphere with a volume fraction of 15%, and intermediate B was obtained; intermediate B and 20% nitric acid solution were mixed in a mass ratio of 1:3, the ball-to-material ratio was 15:1, and the mixture was ground at 200rpm for 18 minutes, and then a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B was added, and the grinding was continued for 18 minutes, filtered, and dried at 100°C for 6 hours to obtain an ultrafine filler; the bacterial solution was composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content was 5×10 12 The remaining steps are the same as those in Example 2.
[0027] Comparative Example 4 The difference between Comparative Example 4 and Example 2 is that step (1) is changed to: sort the kitchen residues, remove the bones, put them into a press, press them to a moisture content of 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, put them into a crusher, crush them to a particle size of 2 mm, and granulate them to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment them at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry them at 100°C for 10 h, heat them to 220°C, and semi-carbonize them. 6h, enter the air flow mill, the air flow is 200℃ with a volume fraction of 15% carbon dioxide-nitrogen, grind for 25min to obtain intermediate B; intermediate B and 20% nitric acid solution are mixed in a mass ratio of 1:3, the ball-to-material ratio is 15:1, and the grinding is carried out at 200rpm for 18min, and then a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B is added, and the grinding is continued for 18min, filtered, and dried at 100℃ for 6h to obtain an ultrafine filler; the bacterial liquid is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.
[0028] Comparative Example 5 The difference between Comparative Example 5 and Example 2 is that step (1) is changed to: sort the kitchen residues, remove the bones, enter the press, press until the moisture content is 25% to obtain a wet material, add 0.4 times the mass of cement and 1.2 times the mass of fly ash to the wet material, enter the crusher, crush to a particle size of 2 mm, and granulate to obtain an intermediate A with a diameter of 8 mm; mix the bacterial liquid and the intermediate A at a mass ratio of 1:1000, ferment at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dry at 100°C for 10 h, and then heat to 220°C. , semi-carbonized for 6 hours, and then put into a jet mill, the airflow is 200℃ with a volume fraction of 15% carbon dioxide-nitrogen, after pulverizing for 25 minutes, take out, and activate at 450℃ for 25 minutes in an atmosphere of 15% carbon dioxide-nitrogen to obtain intermediate B; intermediate B and a 4% sodium nitrite aqueous solution with a mass fraction of 4 times the mass of intermediate B are further ground for 18 minutes, filtered, and dried at 100℃ for 6 hours to obtain an ultrafine filler; the bacterial liquid is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 The powder feeding pressure of the air flow mill is 0.4 MPa, and the crushing pressure is 0.9 MPa; the remaining steps are the same as those in Example 2.
[0029] Comparative Example 6 The difference between Comparative Example 6 and Example 2 is that step (1) is omitted, and step (3) is changed to: under stirring at 300 rpm, a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor are added, and the mixture is kept warm at 68° C. for 1.5 h. During the heat preservation process, 1 / 5 coarse aggregate and 1 / 5 fine aggregate are continuously added. The rotation speed is adjusted to 60 rpm, and the heat preservation is continued for 2 h. During the heat preservation process, 1 / 5 coarse aggregate and 1 / 5 fine aggregate are continuously added, and then the mixture is cooled to room temperature, cement, ultrafine filler, and deionized water are added, and after stirring for 5 min, the remaining coarse aggregate and fine aggregate, microsilica powder, and sodium nitrate are added, and stirred for 10 min to obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, deionized water, and sodium nitrate is 420:30:120:250:6:170:3; and the remaining steps are the same as those in Example 2.
[0030] Comparative Example 7 The difference between Comparative Example 7 and Example 2 is that step (2) is omitted, and step (3) is changed to: adding cement, ultrafine filler, and deionized water under stirring at 60 rpm, stirring for 5 minutes, adding coarse aggregate, microsilica powder, and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, and stirring for 10 minutes to obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, cement, fine aggregate, ultrafine filler, microsilica powder, deionized water, and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine is 420:120:250:100:6:170:30; the remaining steps are the same as those in Example 2.
[0031] Effect example Table 1 below shows the performance analysis results of the anti-cracking and anti-corrosion concrete using Examples 1 to 3 of the present invention and Comparative Examples 1 to 7.
[0032] Table 1 From the comparison of the experimental data of the embodiment and the comparative example, it can be found that the present invention utilizes kitchen residues, cement and fly ash through semi-carbonization to obtain an aggregate-like filler with apparent strength and certain toughness inside, which can improve the anti-cracking performance of concrete. Its surface has a porous structure. After being ground and modified by nitric acid, the content of surface active groups is increased. The inorganic rust inhibitor is used as a raw material and ground again to form an ultrafine particle size. At the same time, the inorganic rust inhibitor is fixed and filled in the holes, and the release of the inorganic rust inhibitor is effectively controlled to achieve the anti-corrosion effect of the concrete. In the process of preparing concrete, the present invention also adds a pre-emulsion precursor prepared by hexaethylcyclotrisiloxane and N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine to form a tough network structure inside the aggregate and cement, thereby improving the anti-cracking performance of the concrete. The ultrafine filler is adsorbed on the surface of the network structure and self-stacked, thereby prolonging the penetration time of the rust inhibitor and further improving the anti-corrosion performance of the concrete.
[0033] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing crack-resistant and corrosion-resistant concrete, characterized in that: The method comprises the following preparation steps: (1) Kitchen residues were sorted, bones were removed, and the residues were fed into a press and pressed to a moisture content of 25% to obtain wet materials. Cement 0.4 times the mass of the wet materials and fly ash 1.2 times the mass of the wet materials were added, and the residues were fed into a crusher and crushed to a particle size of 2 mm. Intermediate material A with a diameter of 8 mm was obtained by granulation. The bacterial liquid and intermediate material A were mixed at a mass ratio of 1:1000, fermented at 43°C, 80 rpm, and a ventilation volume of 6 L / min for 56 h, dried at 100°C for 10 h, heated to 220°C, semi-carbonized for 6 h, and fed into an air flow mill with an air flow of 200°C and a volume fraction of 15% carbon dioxide-nitrogen. Gas, crush for 25 minutes, take out, activate at 450℃ for 25 minutes in a 15% volume fraction carbon dioxide-nitrogen atmosphere to obtain intermediate B; mix intermediate B and 20% mass fraction nitric acid solution in a mass ratio of 1:3, grind at 200rpm for 18 minutes with a ball-to-material ratio of 15:1, add 4% mass fraction sodium nitrite aqueous solution 4 times the mass of intermediate B, continue grinding for 18 minutes, filter, and dry at 100℃ for 6 hours to obtain ultrafine filler; the bacterial solution is composed of white mold, lactic acid bacteria, white rot fungi, and black Aspergillus in a volume ratio of 1:1:1:1, and the bacterial content is 5×10 12 / mL; the powder feeding pressure of the air flow mill is 0.4MPa, and the crushing pressure is 0.9MPa; (2) Hexaethylcyclotrisiloxane, N-(hydroxyethyl)-N,N-bis(trimethoxysilylpropyl)amine, perchlorate O-25, and deionized water were mixed in a mass ratio of 50:25:0.5:89, stirred at 600 rpm for 22 min, and homogenized at a pressure of 30 MPa for 1 min to obtain a pre-emulsion precursor; (3) Under stirring at 300 rpm, add a pre-emulsion precursor and 0.09 times the mass of dodecylbenzene sulfonic acid of the pre-emulsion precursor, keep warm at 68°C for 1.5 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, adjust the rotation speed to 60 rpm, continue to keep warm for 2 hours, continuously add 1 / 5 coarse aggregate and 1 / 5 fine aggregate during the insulation process, then cool to room temperature, add cement, ultrafine filler, and deionized water, stir for 5 minutes, add the remaining coarse aggregate and fine aggregate, and microsilica powder, stir for 10 minutes, and obtain crack-resistant and corrosion-resistant concrete; the mass ratio of the coarse aggregate, pre-emulsion precursor, cement, fine aggregate, ultrafine filler, microsilica powder, and deionized water is 420:30:120:250:100:6:170.
Citation Information
Patent Citations
Anti-cracking recycled concrete and preparation method thereof
CN113735520A
Anti-cracking and anti-corrosion concrete and preparation method thereof
CN118026590A
Anti-cracking and Anti-aging waterproof decorative integrated coating and preparation method therefor
WO2023168809A1